UV-B radiation on lemons enhances antifungal activity of flavedo extracts against Penicillium digitatum - Ruiz, Verónica Eugenia (2017)
UV-B radiation (UVBR) treatment, previously standardized in our laboratory, contributes to prevent green mold caused by Penicillium digitatum on postharvest lemons. Here, antifungal activity of flavedo extracts from irradiated and non-irradiated lemons was assayed against P. digitatum; also, compounds that could be responsible for this action were searched. The flavedo extracts from UV-B exposed lemons (UVBLE) exhibited a higher antimicrobial activity than extracts from control lemons (CLE). Conidia treated with UVBLE showed a time dependent inhibition of germination and oxygen consumption, a markedly increase in ROS and TBARS production and in membrane permeability. By chemical analysis of lemon extracts, two fractions (A and B) that responded to the irradiation were detected, showing a decrease in Fraction A and an increase in Fraction B. Fraction B showed higher antioxidant and antifungal activities in comparison to Fraction A. Both fractions were complex samples enriched in flavonoids. The specific composition of each fraction could explain the difference in the biological activities, and also the higher efficiency of UVBLE to inhibit in vitro the pathogen compared to CLE. Based on our results, UV-B radiation treatment can intensify natural defenses of flavedo lemon by eliciting phenolic compounds synthesis, among other processes.